Evaluation of the "control over reinforcement" component in functional communication training. - Kahng, S (1997)
The effectiveness of functional communication training (FCT) as a treatment for behavior disorders has been attributed to a number of variables, one of which is the individual's ability to exert control over the delivery of reinforcement. We evaluated this component of FCT by exposing individuals to conditions in which their behavior either did or did not affect the delivery of reinforcement. Three adults with mental retardation who engaged in self-injurious behavior (SIB) participated. Following a functional analysis of their SIB, the effects of FCT were compared to those of noncontingent reinforcement (NCR) in a multielement design. The amount of reinforcement during both conditions was equated by yoking the schedule of reinforcement during NCR sessions to that in effect during FCT sessions. Results indicated that FCT and NCR were equally effective in reducing the SIB of all participants and suggest that control over reinforcement delivery may not affect the degree to which FCT produces behavioral suppression. However, a different benefit of FCT was evident in the results: More consistent increases in the alternative response were observed during the FCT condition than during the NCR condition.